Effect of Alkaline Earth Metal (M= Sr, Ca and Mg) Substitution on Dielectric Properties of Ba₁₋ₓMₓPbO₃ Ceramics - Ari Sulistyo, Rini (2002)
BaPbO₃-based cerarntc have been the subject of numerous laboratory investigations, structurally and electrically. BaPbO₃ is a polycrystalline that possesses perovskite crystal structure, which is similar to the prototype dielectric ceramic i.e. BaTiO₃ structure. It is obviously noticed that suitable substitution on a system, enables us to change electrical properties of material to obtain specific requirement.